In vitro effects of Coriandrum sativum, Tagetes minuta, Alpinia zerumbet and Lantana camara essential oils on Haemonchus contortus - Iara Tersia Freitas Macedo (Revista Brasileira de Parasitologia Veterinária, 2013)
Phytotherapy can be an alternative for the control of gastrointestinal parasites of small ruminants. This study evaluated the efficacy of Alpinia zerumbet , Coriandrum sativum , Tagetes minuta and Lantana camara essential oils by two in vitro assays on Haemonchus contortus , an egg hatch test (EHT) and larval development test (LDT). No effect was observed for L. camara in the EHT. A. zerumbet , C. sativum and T. minuta essential oils exhibited a dose-dependent effect in the EHT, inhibiting 81.2, 99 and 98.1% of H. contortus larvae hatching, respectively, at a concentration of 2.5 mg mL –1 . The effective concentration to inhibit 50% (EC50) of egg hatching was 0.94, 0.63 and 0.53 mg mL –1 for A. zerumbet , C. sativum and T. minuta essential oils, respectively. In LDT, L. camara , A. zerumbet , C. sativum and T. minuta at concentration of 10 mg mL –1 inhibited 54.9, 94.2, 97.8 and 99.5% of H. contortus larval development, presenting EC50 values of 6.32, 3.88, 2.89 and 1.67 mg mL –1 , respectively. Based on the promising results presented in this in vitro model, it may be possible use of these essential oils to control gastrointestinal nematodes. However, their anthelmintic activity should be confirmed in vivo.